Peranan religiusitas dan kecerdasan spiritual terhadap peningkatan kesejahteraan psikologis - Nusaibah Nur Furqani (Universitas Muhammadiyah Malang, 2021)
Psychological well-being is an indicator of individual welfare to meet the criteria for positive psychological functioning. One of the factors that can fulfill the positive psychological function is having a high religious spirit which is assisted by the ability to interpret life which cannot be separated, such as carrying out the values ​​of truth and goodness in order to lead to prosperity. The purpose of this study was to determine the relationship between religiosity and psychological well-being and the role of spiritual intelligence in mediating the relationship between religiosity and psychological well-being. The research design used a quantitative approach measured using the dimension of religiousty scale, spiritual intelligence questionnaire (SQ) and the scale of Psychological Well-being (SPWB). The subjects used were aged 20-35, as many as 110 women who joined the malut recitation group. Data analysis using Mediated Multiple Regresson. The results showed the value of β = 0.315 P = 0.2822, which means that spiritual intelligence does not mediate the relationship between religiosity and psychological well-being. Individuals with high religiosity are proven to be able to increase psychological well-being without the role of spiritual intelligence.